Antenna Pattern Correction Technique Based on an Adaptive Array Algorithm - Viikari, V.; Kolmonen, V.-M.; Salo, J.; Raisanen, A.V. (IEEE transactions on antennas and propagation, 2007)
An antenna pattern correction technique is presented that is based on an adaptive array algorithm. In the method, the antenna pattern of the antenna under test (AUT) is measured several times at different positions in the quiet-zone. The corrected antenna pattern is obtained by taking a weighted average of the measured patterns. An array synthesis algorithm is employed for obtaining the averaging weights at each rotation angle of the AUT. The weights are adapted specifically for a given AUT. The adaptive array correction technique is demonstrated in a hologram based compact antenna test range (CATR) at 310 GHz with both a synthetic antenna and a physical test antenna. For verification, the accuracy provided by the adaptive array correction technique is compared to that provided by uniform weighting.